Pregnancy Expectations and Experiences among Women in Southeast Ohio: Implications for Clinical Practice - Caroline Kingori; Kay-Anne Darlington; Jamie Kuhlman; Tania Basta (Ohio Journal of Public Health, 2019)
Background/Objectives: Nearly 4 million women experience pregnancy every year in the United States. While there is research about medical outcomes related to pregnancy, especially in the context of disease, there is a dearth of research related to pregnancy expectations. Methods: This qualitative study explored women’s expectations and experiences of pregnancy in Southeast Ohio. Participants attending a clinic were recruited for individual interviews onsite at the physician's office. Interviews were audio recorded and transcribed verbatim. Codes, in the form of descriptive labels such as words or brief phrases, were developed based on entire interviews. Results: Results indicate that women experience pregnancy on a continuum, some women enjoyed the experience, some were ambivalent, while others did not enjoy the experience. Furthermore, some women reported that their expectations for pregnancy matched their experience(s), while others felt that their expectations did not match their experience. Some women also felt “judged” by other women and even health care providers if they did not “love” the experience. Conclusions: Women experience pregnancy in a variety of ways, therefore, it is important that health care providers be sensitive to the notion that not all women enjoy the process, but they all want the same outcome of a healthy child. While it is important for health care providers to assess the physical health of the mother and the unborn child, this study demonstrated that it is also important to assess what an expectant mother knows about pregnancy and what she expects to happen.
Keywords: Pregnancy; Appalachia; reproductive health; contraception